A real‐life pilot study of the clinical application of pharmacogenomics testing on saliva in epilepsy - Antonella Riva; Roberta Roberti; Gianluca D'Onofrio; Maria Stella Vari; Elisabetta Amadori; Valentina De Giorgis; Caterina Cerminara; Nicola Specchio; Nicola Pietrafusa; Mario Tombini; Giovanni Assenza; Silvia Cappanera; et al. (Epilepsia Open, 2023)
Abstract Response to antiseizure medications (ASMs) can be influenced by several gene polymorphisms, causing either lower efficacy or higher occurrence of adverse drug reactions (ADRs). We investigated the clinical utility of salivary pharmacogenomic testing on epilepsy patients. A commercialized pharmacogenomic salivary test was performed in a cohort of epileptic patients. Genetic variants on five genes (i.e., CYP1A2, CYP2C9, CYP2C19, EPHX1, and ABCB1) involved in common ASMs metabolism were selected. Twenty‐one individuals (median age [Q1–Q3]: 15 [6.5–28] years) were enrolled. Six patients harboring the homozygous *1F allele in CYP1A2 could have reduced chance of response to stiripentol due to fast metabolism. CYP2C9 had reduced activity in 10 patients (alleles *2 and *3), potentially affecting phenytoin (PHT), phenobarbital (PB), primidone, lacosamide (LCM), and valproic acid metabolism. Seven patients, carrying the *2 allele of CYP2C19, had an increased risk of ADRs with clobazam (CLB), PB, PHT, LCM, brivaracetam; while one individual with the *17 allele in heterozygosity reported a CLB fast metabolism. Six patients showed a CC polymorphism of EPHX1 associated with the impaired efficacy of carbamazepine. ABCB1 polymorphisms related to drug‐resistance (3435 CC) or drug‐sensitive phenotype (CT or TT) were found in 6 out of 7 patients. Pharmacogenomic testing on saliva proved easy and safe in clinical practice to convey information for the management of epileptic patients, especially those resistant to treatment or sensitive to severe ADRs.